Kajian Kinerja Pelaksanaan Pengurusan Persetujuan Bangunan Gedung (PBG) pada Dinas PUPR Kabupaten Padang Pariaman - Rino, Rino; Mulyani, Rini; Khadavi, Khadavi (Jurnal Talenta Sipil, 2024)
In 2022, the implementation of PBG processing which has been carried out by the Padang Pariaman DPUPR in the field of Human Settlement does not comply with the time period based on the established regulations. In this regard, the author conducted research on the factors that influence its implementation, the obstacles faced, as well as potential improvements or recommendations to increase the efficiency and effectiveness of the process. The research method used is a qualitative method by distributing questionnaires and interviews with informants. The dominant factor is timeliness in implementing PBG arrangements; facilities and infrastructure; HR; and initiative. In the Likert Scale assessment, the highest result was obtained in the Disagree assessment, namely 5.57%. The results of the identification of indicators and evaluation results have been validated with experts so that the author provides recommendations to the field of creative work of the Padang Pariaman Regency DPUPR to increase the number of human resources capable of carrying out PBG implementation in accordance with applicable regulations. The Padang Pariaman Regency DPUPR Job Creation Sector must have the facilities and infrastructure to carry out the duties of implementing PBG in serving the community. And the Cipta Karya sector must have the initiative to provide information to the public about PBG and provide licensed experts to help the community complete the PBG requirements.